Mass Spectrometry in Biophysics: Conformation and Dynamics of Biomolecules - Kaltashov (Igor A); Eyles (Stephen J) (2005)
Mass Spectrometry ; Biophysics ; Biomolecules
22.5
Keywords: Mass Spectrometry ; Biophysics ; Biomolecules